ISLAMIC VALUES IN THE CIVIL SOCIETY OF UZBEKISTAN - Ergasheva Muattar Nuriddinovna (Scholar Express Journal, 2022)
In the context of the globalization of the modern world, each country that is part of the world community, in its own way, implements the essential features of the future world civilization. The countries of Eastern and Eurasian civilizations, resisting the process of inevitable globalization and transformation of their socio-economic, political and spiritual structures, at the same time are looking for ways and means of combining heterogeneous values
Keywords: Islamic values; civil society; multi-confessional; confessional tolerance